Morphological transparency and markedness matter in heritage speaker gender processing: an EEG study - Luque, Alicia; Rossi, Eleonora; Kubota, Maki; Nakamura, Megan; Rosales, César; López-Rojas, Cristina; Rodina, Yulia; Rothman, Jason (Frontiers in Psychology, 2023)
The present study investigated the qualitative nature of grammatical gender knowledge and processing across heritage speakers (HSs) of Spanish living in the United States (US). Forty-four adult Spanish HS bilinguals participated in the study. Each completed a behavioral gender assignment task as well as a grammaticality judgment task (GJT) while their brain activity was being recorded using electroencephalography (EEG). The EEG GJT task was comprised of grammatical and ungrammatical sentences, including gender violations on inanimate nouns, where transparency of the morpho(phono)logical cue and markedness were manipulated. Our results revealed that gender violations elicited the typical P600 effect across all relevant conditions, indicating that our HSs’ grammatical representations, as well as processing for grammatical gender, are qualitatively similar to that of other types of Spanish-dominant native speakers. Given our manipulations, results also indicate that both morphological transparency and markedness play significant roles in how gender is processed. Notwithstanding, our results do differ from what has been reported for Spanish-dominant native speakers in that the P600 was accompanied by a biphasic N400 effect. We interpret this pattern as further evidence that HS bilingual experience modulates some aspects of morphosyntactic processing, particularly conferring a greater weighting/reliance on morphology. The results of our study underscore the value of incorporating neurolinguistic online processing methods to understand best what underlies HS bilingual competence and processing outcomes.